RISKS AFFECTING INVESTMENT ACTIVITY AND THEIR CLASSIFICATION - Sobirjonova Nodira Rustamjon qizi (Modern American Journals, 2025)
The investment process is one of the important factors for the sustainable development and growth of the economy. Improving the investment climate, attracting investment and developing economic activity are among the priorities of any country. However, the investment process is associated with various risks, the effective assessment and minimization of which is crucial for ensuring economic stability. The economy of Uzbekistan is pursuing an active policy aimed at rapid development and improving the investment climate. A number of reforms are being implemented in the country to improve the investment climate. At the same time, the issue of effective management of economic, legal and financial risks remains an important task. The role of state policy, legal guarantees, financial instruments and technologies in this process is of great importance. In the modern global economy, factors such as economic instability, geopolitical threats, inflation, exchange rate fluctuations, the complexity of market competition, natural disasters and pandemics increase investment risks. Therefore, before investing, investors are required to accurately assess risks and develop effective strategies to reduce their impact on economic activity.